Isolation and Functional Characterization of Yeasts from Fermented Plant Based Products - Dilara Devecioglu; Anı Kuscu; Funda Karbancioglu-Guler (Fermentation)
Yeasts isolated from fermented plant-based sources—boza, pickles, and chickpeas—were evaluated for probiotic potential. Among 18 colonies, seven isolates showing no hemolytic activity were selected and identified: Pichia kudriavzevii (four isolates), Kazachstania exigua, Hanseniaspora uvarum, and Saccharomyces cerevisiae. Most isolates were able to survive under low pH and bile salt conditions, simulating the environment of the gastrointestinal tract (5.62–8.59 log CFU/mL) and tolerated NaCl concentrations up to 6–8% (w/v). All isolates exhibited antibiotic resistance; however, their susceptibility to antifungals varied. While P. kudriavzevii DD_B_M88 exhibited the highest hydrophobicity (63.07%), isolate auto-aggregation increased to 53–95% after 24 h. Most isolates showed a great capability to co-aggregate with pathogens and inhibited them significantly (up to 98.72%), except for S. cerevisiae DD_NB_M90. The selected three isolates and their cell-free supernatants, up to a certain concentration, showed no significant cytotoxicity on Caco-2 cell line. Eventually, six isolates, excluding S. cerevisiae DD_NB_M90, fulfilled the probiotic criteria, and can serve as probiotic starter cultures for alternative food production.